Human Immunodeficiency Virus type 1 (HIV-1) and Breastfeeding Science, Research Advances, and Policy - Kourtis, Athena P.; Bulterys, Marc.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
zzzzzz
Breastfeeding and transmission of HIV-1: Epidemiology and Global Magnitude -- Breastfeeding and Transmission of viruses other than HIV-1 -- Breastfeeding among HIV-1-infected women: Maternal health outcomes and social repercussions -- Virologic determinants of breast milk transmission of HIV-1 -- HIV-1 resistance to antiretroviral agents: Relevance to mothers and infants in the breastfeeding setting -- Animal models of HIV transmission through breastfeeding and pediatric HIV infection -- Antiretroviral pharmacology in breast milk -- HIV-1 diagnosis of the breastfed infant -- The immune system of breast milk: antimicrobial and anti-inflammatory properties -- Humoral /mucosal/innate immunity in the breast milk in the context of HIV-1 infection -- Cellular immunity in breast milk: Implications for Postnatal Transmission of HIV-1 to the infant -- Antiretroviral drugs during breastfeeding for the prevention of postnatal transmission of HIV-1 -- Immune Approaches for the prevention of breast milk transmission of HIV-1 -- Non-antiretroviral approaches to prevention of breast milk transmission of HIV-1: Exclusive breastfeeding, early weaning, treatment of expressed breast milk -- Breast milk micronutrients and mother-to-child transmission of HIV-1 -- Historical perspective of African-based research on HIV-1 transmission through breastfeeding: The Malawi experience -- Breastfeeding and HIV infection in China -- The role of the President$1 (Bs Emergency Plan for AIDS Relief (PEPFAR) in infant and young child feeding guideline development and program implementation -- Should women with HIV-1 infection breastfeed their infants? Balancing the scientific evidence, ethical issues and costs-policy considerations -- HIV-1 and Breastfeeding in the United States -- Epilogue. The future of breastfeeding in the face of HIV-1 infection: Science and Policy.s
Keywords: Medicine; Immunology; Medical virology; Maternal and infant welfare; Emerging infectious diseases; Epidemiology; Medicine & Public Health; Medicine/Public Health, general; Epidemiology; Maternal and Child Health; Infectious Diseases; Virology; Immunology